The state of knowledge about the beginnings of the Cistercian abbey in Henryków in historiography of the late Middle Ages Renaissance - Michalska, Monika (Saeculum Christianum. Pismo Historyczne, 2021)
The cloister of Cistercians in Henryków possesses the complex founding traditions, both monastic and secular. The most complete vision of the origins of the monastery in Henryków gives us the Book of Henryków. The Book of Henryków delivers quite a complicated picture of the foundation. In the foundation of the cloister as many as three persons took part: the notary Nicholas, prince Henry the Bearded and Henry the Pious. According to the author of the first part of the Book of Henryków, the prince Henry the Pious was the only founder of the cloister. The analysis of late medieval and renaissance chronicles give us a quite different picture of its foundation. There are two leading concepts. The first sustained thesis of princely foundations. Its originator was Peter of Byczyna the author of the Chronica Principium Poloniae. The second concept was created by Jan Dlugosz, who ascribed the foundation of Henryków to the notary Nicholas.